(untitled) (Research, Society and Development, 2024)
This research aims to analyze the effect of corporate governance and the Audit Committee, on disclosing the quality of information of publicly traded companies listed on [B]3, with financial information in the reference form and in the Economática database ® for the years 2014 to 2023. Study is based on qualitative disclosure of information and corporate governance, combined with the Audit Committee based on disclosure and stakeholder theories and audit committee analysis. The research is descriptive, quantitative, documentary, with the population being companies listed on [B]3 S.A., made up of 400 companies. To compose the sample, 320 publicly traded companies were selected with information on the constructs raised. The results showed that there are significant statistical differences with the presence of the Audit Committee and companies with external audits conducted by the big four, which favors the quality of the information that is disclosed, compared to companies that are not audited by them. In the results it was possible to verify that more profitable companies have greater commitment to disclosures and, therefore, are more likely and committed to the responsibility of disclosing information. The research contributes to the understanding that, in Brazil, the majority of companies have highly concentrated ownership, the pressure exerted by controlling shareholders may be reducing the positive impact of corporate governance practices.